Intervensi Promosi Kesehatan Melalui Media Sosial Tiktok terhadap Pengetahuan, Sikap dan Niat Berhenti Merokok pada Remaja - Winda Astuti Alawiyah; Syamsulhuda Budi Musthofa; Sri Achadi Nugraheni (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effect of health promotion interventions via TikTok social media on knowledge, attitudes, and intentions to quit smoking among high school teenagers in Karawang Regency. The method used is a quasi-experiment method with a non-equivalent pre-test post-test control group design. The results of the study showed that there was an increase in the average knowledge, attitudes, and intentions in the intervention group compared to the control group, with a p-value of 0.000. In conclusion, health promotion interventions through social media TikTok affect knowledge, attitudes, and intentions to stop smoking among high school teenagers in Karawang Regency. Keywords: Social Media, Knowledge, Teenagers, Cigarettes